Challenges in Fabricating Solid Oxide Fuel Cell Stacks for Portable Applications: A Short Review - Raduwan, Nor Fatina; Muchtar, Andanastuti; Somalu, Mahendra Rao; Baharuddin, Nurul Akidah; SA, Muhammed Ali (International Journal of Integrated Engineering, 2018)
Despite being the most efficient and quiet operation type of fuel cells, solid oxide fuel cells (SOFCs) deal with several constraints in terms of fabrication cost, material selection and durability issues due to their high operating temperature. The high operating temperature of SOFCs limits their stationary and large-scale applications. Moreover, these constraints restrict the commercialization of portable SOFCs. Therefore, the operation temperature of SOFCs must be reduced to overcome the aforementioned problems. However, this task is challenging because the operation temperature mainly affects the material preparation and the stack design to produce the electrical power needed for small-scale applications. This paper provides an overview of the challenges faced by each component such as the materials, the design of stack, fabrication cost and related research in fabricating high power SOFC stacks.